Virginity revisited : configurations of the unpossessed body - MacLachlan, Bonnie; Fletcher, Judith (Phoenix. Supplementary volume (Toronto, Ont.). Studies in Gender., 2007)
"Virginity Revisited is a collection of essays that examines virginity not as a physical reality but as a cultural artefact. By situating the topic of virginity within a range of historical 'moments' and using a variety of methodologies, Virginity Revisited illuminates how chastity provided a certain agency, autonomy, and power to women. This is a study of the positive and negative features of sexual renunciation, in ancient Greek divinities and mythical women, in Rome's Vestal Virgins, in the Christian martyrs and Mariology in the medieval and early modern period, and in Grace Marks, the heroine of Margaret Atwood's novel Alias Grace."--Jacket